Rancang Bangun Alat Kendali Aroma Ruangan Menggunakan Pengharum Ruangan Otomatis Berbasis Mikrokontroler - Klen Tupan; Joko Saputro; Raditya Galih Whendasmoro (FIKOM Universitas Bung Karno, 2022)
The average time spent indoors while working or doing activities tends to be long. A room needs a sense of comfort to support activities in the room. A comfortable room is not only influenced by attractive furniture and decorations, but the smell in the room is one of the most important factors to make residents feel comfortable when they are in it. Rooms that give off an unpleasant odor can come from bacteria that have long settled on decorative items and can cause an unnatural smell and disturb comfort. Therefore, a tool is needed to neutralize odors in unpleasant room conditions with an air freshener that can work automatically, so that the room smells good at all times and is consistent with the tool's working time. To overcome this, this study aims to design and build an automatic air freshener based on Arduino Uno using the Real Time Clock (RTC) module.